Structure, magnetic and electrical properties of disordered double perovskite Pb2CrMoO6. (February 2015) - Zhao, H.F.; Cao, L.P.; Song, Y.J.; Feng, S.M.; Shen, X.; Ni, X.D.; Yao, Y.; Wang, Y.G.; Jin, C.Q.; Yu, R.C.
Abstract: We prepared Pb2 CrMoO6 under high pressure and high temperature. The sample has a heavily or fully disordered double perovskite structure ( Pm-3m, a =3.9472 Å). It shows a weak ferromagnetic behavior ( T C 33 K) and a significant low magnetization ( 0.095 μB /f.u. at 7 T and 5 K), which is discussed based on the cation disorder. The temperature dependence of the electrical resistivity of Pb2 CrMoO6 exhibits a semiconducting behavior, which could be well understood by the 3D variable range hopping model. No significant magnetoresistance was observed in this sample. Highlights: A new double perovskite Pb2 CrMoO6 was prepared under high pressure and high temperature conditions. Structure, magnetic and electrical properties of synthesized Pb2 CrMoO6 were investigated.. The measured properties of Pb2 CrMoO6 are discussed based on cation disorder.